TÓLEPBERGEN QAYIPBERGENOVTIŃ “TÚSINIKSIZLER” ROMANINDA NAQIL-MAQALLARDIŃ QOLLANILIW ÓZGESHELIKLERI - Kırkbaev, Arıslanbay Sultanbay ulı (INTERNATIONAL CONFERENCES, 2023)
This article is about the proverbs about animals, which were used in the novel “Tusiniksizler” by Tulepbergen Kayipbergenov. Proverbs about animals were used to express the symbolic meaning.